Pseudoscience : a critical encyclopedia - Regal, Brian (Greenwood Press, 2009)
More than just a collection of factual entries, this resource explores the difference between scientific and pseudoscientific pursuits. Turning metals into gold, reading head bumps for personality clues, finding water in the ground with a stick; at some point, all of these were considered legitimate scientific practices. But efforts to pass similar activities off as genuinely scientific are by no means confined to a less enlightened age. From homeopathy to UFO hunting to Creationism, the practice of stamping unscientific activities with the imprimatur of science is alive and well today. What makes science science? How do we tell which assertions, beliefs, and methods are scientifically sound, and which are not? This reference work gets at the heart of these questions by helping readers understand how the scientific method works, how to critically analyze all kinds of "evidence," and how to sort through long-running myths and current pseudoscience controversies. Ranging from the dawn of history to the present and across world cultures, Pseudoscience uses a field of endless fascination as a means of driving home the importance of solid scientific reasoning. The encyclopedia spans the full spectrum of scientific and nonscientific pursuits, from chemistry, biology, psychology, and medicine to eugenics, religion, cryptozoology, the occult, and paranormal activities. Specific entries focus on general concepts of science, the lives of individuals, and claims of abilities. Throughout, these entries go beyond simply stating facts by constantly engaging readers in a discussion about the very nature of true scientific discovery